Foucault's pendulum - Eco, Umberto (San Diego : Harcourt Brace Jovanovich, 1989)
Using a computer, three editors attempt to write a Templar Plan as a joke, they think...until people begin to disappear.
Translation of: Il pendolo di Foucault., card
"A Helen and Kurt Wolff book."
Keywords: Occult fiction; Voodooism -- Fiction; Religions -- Fiction; Idolatry -- Fiction; Foucault's pendulum -- Fiction; Alchemy -- Fiction; Thought and thinking -- Problems, exercises, etc. -- Fiction; Psychological fiction; Occult fiction